Barriers to the evaluation of systematic conservation plans: Insights from landmark Australian plans - McIntosh, EJ (Elsevier, 2019)
The evaluation of conservation programs is often inhibited by barriers such as time constraints and a lack of funding. Through an exploration of two internationally influential systematic conservation planning activities conducted in Australia in the 1990s and 2000s, I demonstrate this is also true for conservation planning programs. Forestry agreements in North East New South Wales and the rezoning of the Great Barrier Reef Marine Park popularised the now widely used planning software packages C-Plan and Marxan. Through 37 semi-structured interviews with senior stakeholders involved in decision-making around both plans, I examined barriers to evaluation, the factors underpinning these barriers, and, in the absence of program-wide evaluations, stakeholder perceptions of the effectiveness of the plans. My findings confirmed that the primary barriers to the evaluation of conservation planning exercises are a lack of suitable monitoring data, resource limitations and inadequate preparation. Respondents also shed light on the factors which shaped these barriers in a conservation context, such as the need for political expediency, a loss of momentum post-plan, and the presence or absence of necessary leadership. Perceptions of the effectiveness of the plans reflected interpretations of a) whether the planning process followed good practice, b) the fact a planning result was agreed upon and implemented, c) the longer-term influence of the plan, and, in contrast to much of the current literature on these case studies, d) the consequences of industry restructuring.